2018
DOI: 10.1007/s11427-017-9283-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficiency of a begomovirus to cross the midgut of different species of whiteflies results in variation of virus transmission by the vectors

Abstract: Begomoviruses are important crop viral disease agents, and they are transmitted by whiteflies of the Bemisia tabaci complex. Although the transmission of begomoviruses by whiteflies has been studied for many years, the mechanisms governing differential transmission of begomoviruses by different species of the Bemisia tabaci complex remain largely unknown. Here we firstly compared the transmission efficiency of tobacco curly shoot virus (TbCSV) by four species of the B. tabaci complex and found that Asia II 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Moreover, we show that the relative amounts of PeVYV-2 and PeWBVYV in the hemolymph of the non-transmitting MEAM1 and MED, respectively was much lower compared to relative amounts of PeWBVYV in the hemolymph of MEAM1. Mere ability of persistent viruses to cross the midgut barrier and presence in the hemolymph of their insect vectors does not guarantee its transmission (20, 35, 40, 41) but virus quantities above a threshold level within the hemolymph is crucial for its successful transmission (17, 24, 42). Thus, the non-transmission of PeWBVYV by MED whiteflies is possibly due to lower translocation of PeWBVYV across the midgut barrier of the MED whiteflies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we show that the relative amounts of PeVYV-2 and PeWBVYV in the hemolymph of the non-transmitting MEAM1 and MED, respectively was much lower compared to relative amounts of PeWBVYV in the hemolymph of MEAM1. Mere ability of persistent viruses to cross the midgut barrier and presence in the hemolymph of their insect vectors does not guarantee its transmission (20, 35, 40, 41) but virus quantities above a threshold level within the hemolymph is crucial for its successful transmission (17, 24, 42). Thus, the non-transmission of PeWBVYV by MED whiteflies is possibly due to lower translocation of PeWBVYV across the midgut barrier of the MED whiteflies.…”
Section: Discussionmentioning
confidence: 99%
“…The circulative pathway of the virions after ingestion by its specific aphid or whitefly vector involves recognition and adsorption to the membrane of the insect hindgut or posterior midgut for aphids (7,8) while the filter chamber or anterior midgut for whiteflies (9,10); internalization and translocation across the gut epithelial cells into the hemocoel by receptor mediated endocytosis (11)(12)(13)(14); streaming in the hemocoel to reach the accessory salivary glands for aphids (15) and primary glands for whiteflies (9); and transportation across the glands to the salivary duct (6,16) before egestion onto the next host plants. Throughout this process, the insect midgut (7,17) and the salivary glands (18)(19)(20) of aphids and whiteflies serve as anatomical barriers determining the fate of the virions. Transmissibility of circulative viruses by aphids or whitefly is influenced simultaneously by virus and insect factors.…”
Section: Crinivirus Ipomovirus Torradovirus and Carlavirus Semi-permentioning
confidence: 99%
See 1 more Smart Citation
“…Once ingested through the stylet, these plant viruses move across the mid gut membrane and then via hemolymph translocate to salivary glands and from there these are egested while feeding [15]. In circulation of viruses, mid gut and salivary glands are the main barriers to overcome [16, 17]. Some mid gut proteins and proteins produced by endosymbionts in hemolymph are associated with circulation of viruses in whitefly.…”
Section: Introductionmentioning
confidence: 99%
“…Asia II 1 has been reported to be the most abundant species of whitefly in areas of high incidence of cotton leaf curl disease (CLCuD) in Pakistan and the western region of India. Two recent studies in China [17, 29] directly compared the transmission efficiency of begomoviruses by MEAM1, Asia II 1 and two more species, and showed that among these species Asia II 1 is the most efficient in transmitting both Cotton leaf curl Multan virus (CLCuMuV) and Tobacco curly shoot virus (TbCSV). Apart from differences in transmission efficiency of viruses, these species of whiteflies also differ in insecticide resistance [30] and host plant preference [31].…”
Section: Introductionmentioning
confidence: 99%